Pharmacist and physician insight of vancomycin therapeutic drug-monitoring changes - Eric R. Gregory; Lucy Stun; Matt J. Mason; Nicole M. Wilson; Kassem A. Hammoud (Cambridge University Press, 2022)
The updated vancomycin guideline for treatment of serious methicillin-resistant Staphylococcus aureus infections prompted institutions to convert from trough to area-under-the-curve monitoring. The physician perception of the transition, coupled with that of pharmacists, was measured by pre- and postimplementation surveys. Both groups believed safety would be increased without efficacy changes.